Women and Knowledge in Early Christianity - Tervahauta, Ulla (Vigiliae Christianae, Supplements Ser, 2017)
Intro -- ‎Contents -- ‎Contributors -- ‎Women and Knowledge in Early Christianity: An Introduction (Lehtipuu and Dunderberg ) -- ‎Part 1. Women and Knowledge in Social-Historical Contexts -- ‎Chapter 1. Women and Independent Religious Specialists in Second-Century Rome (Denzey Lewis) -- ‎Chapter 2. "She Destroyed Multitudes": Marcellina's Group in Rome (Snyder) -- ‎Chapter 3. Some Remarks on Literate Women from Roman Egypt (Salmenkivi) -- ‎Part 2. Afterlives of Women in Biblical Narratives -- ‎Chapter 4. Women, Angels, and Dangerous Knowledge: The Myth of the Watchers in the Apocryphon of John and Its Monastic Manuscript-Context (Bull) -- ‎Chapter 5. Jezebel in Jewish and Christian Tradition (Rasimus) -- ‎Chapter 6. Mary and the Other Female Characters in the Protevangelium of James (Luomanen) -- ‎Chapter 7. What Happened to Mary? Women Named Mary in the Meadow of John Moschus (Tervahauta) -- ‎Part 3. Women in Ancient Intellectual Discourse -- ‎Chapter 8. "For Women are Not Worthy of Life": Protology and Misogyny in Gospel of Thomas Saying 114 (Miroshnikov) -- ‎Chapter 9. "Women" and "Heresy" in Patristic Discourses and Modern Studies (Petersen) -- ‎Chapter 10. Astrological Determinism, Free Will, and Desire According to Thecla (St. Methodius, Symposium 8.15-16) (Burns) -- ‎Chapter 11. Monastic Exegesis and the Female Soul in the Exegesis on the Soul (Lundhaug) -- ‎Part 4. The Feminine Principle in Myth and Philosophy -- ‎Chapter 12. Life, Knowledge and Language in Classic Gnostic Literature: Reconsidering the Role of the Female Spiritual Principle and Epinoia (Bak Halvgaard) -- ‎Chapter 13. "Wisdom, Our Innocent Sister": Reflections on a Mytheme (Williams) -- ‎Chapter 14. The Virgin That Became Male: Feminine Principles in Platonic and Gnostic Texts (Turner) -- ‎Bibliography -- ‎Index of Ancient and Medieval Sources